Tumor-Associated Mast Cells in Thyroid Cancer - Carla Visciano; Nella Prevete; Federica Liotti; Gianni Marone (International Journal of Endocrinology)
There is compelling evidence that the tumor microenvironment plays a major role in mediating aggressive features of cancer cells, including invasive capacity and resistance to conventional and novel therapies. Among the different cell populations that infiltrate cancer stroma, mast cells (MCs) can influence several aspects of tumor biology, including tumor development and progression, angiogenesis, lymphangiogenesis, and tissue remodelling. Thyroid cancer (TC), the most frequent neoplasia of the endocrine system, is characterized by a MC infiltrate, whose density correlates with extrathyroidal extension and invasiveness. Recent evidence suggests the occurrence of epithelial-to-mesenchymal transition (EMT) and stemness in human TC. The precise role of immune cells and their mediators responsible for these features in TC remains unknown. Here, we review the relevance of MC-derived mediators (e.g., the chemokines CXCL1/GRO-α, CXCL10/IP-10, and CXCL8/IL-8) in the context of TC. CXCL1/GRO-α and CXCL10/IP-10 appear to be involved in the stimulation of cell proliferation, while CXCL8/IL-8 participates in the acquisition of TC malignant traits through its ability to induce/enhance the EMT and stem-like features of TC cells. The inhibition of chemokine signaling may offer novel therapeutic approaches for the treatment of refractory forms of TC.